Performance Evaluation of Mutual Funds: A Study onSelectedEquity Mutual Fundsin India (International Journal of Food and Nutritional Sciences, 2022)
This study compares the actual performance of Indian mutual funds with their relative performance in order to analyse the efficiency of these funds. The results of this comparison are used to draw conclusions regarding the efficacy of Indian mutual funds. The daily closing net asset values (NAVs) of the various fund schemes were used as the foundation for the calculations that were done in order to determine the returns that were generated by the various fund schemes. The NSE-Nifty index was utilised during the process of developing the market portfolio. The efficiency of mutual funds can be evaluated using a number of different metrics, including ANOVA.